A Cognitive Semantic Analysis of Conceptual Metaphors in Donne’s “A Valediction: Forbidding Mourning” - Abdulla, Ismail A.; Lutfi , Abbas F. (Mitanni Journal of Humanitarian Sciences, 2020)
There has always been a widely held view among literary and linguistic circles that poetic language and naturally occurring language represent two quite different registers; hence, they can by no means be subjected to treatment through the same rout of analysis. Another problem is that poetic language is said to utilize some special figures as meaning construction devices that are called meaning devices, which are purely literary devices and have little value outside literature. This paper aims at analyzing poetic language in terms of the renowned cognitive semantic model known as conceptual metaphor theory which was first prosed for the analysis of everyday language and cognition. Another aim of this study is to prove the fallacy of the traditional view that treated metaphor as an ornamental literary device and one source of linguistic or semantic deviation. Adopting the conceptual metaphor theory, the present research hypothesizes that the conceptual metaphor theory is applicable to the poetic language as well. It is also hypothesized that traditional view toward metaphor is completely false. To achieve the above aims and check the hypotheses, the researchers have analyzed one of the most renowned metaphysical poems by John Donne, titled “A Valediction: Forbidding Mourning.” Through the analysis, it has been concluded that the conceptual metaphor theory is applicable to poetic language as it is to everyday language and the conceptual metaphors are basic, rather than ornamental, for understanding poetry, and for the meaning construction in poetic language as they are in non-poetic one.